The Indonesian sociocultural contexts related to daily occupations of children with cancer during hospitalisation: The parents' perspective. (March 2022) - Buwana, Cahya; Ito, Yuko; Brintnell, E Sharon
Background: The sociocultural phenomenon affecting daily occupations of hospitalised children with cancer in a diverse country like Indonesia is thought-provoking and requires exploration. Objective: This study aims to explore the sociocultural contexts related to daily occupations of children with cancer during hospital admittance from the parents' perspective. Methods: Semi-structured interviews were conducted with parents of children with cancer who had been hospitalised for two weeks or more. The data were collected at the paediatric ward of "Dharmais" National Cancer Center Hospital, Jakarta. The study uses interpretative phenomenological analysis (IPA). Results: Nine parents of children with cancer consented to the study. Three interconnected themes emerged as necessary to the sociocultural context among participants. These involve 'The surrounding human environment as primary encouragement', 'Culture and spirituality as the basic standard' and 'Activity adjustments as new habits'. Conclusions: The themes revealed that the daily occupations of hospitalised children with cancer are strongly encouraged by family and social systems in Indonesia, spiritual aspects of the parents and the occupational changes due to the new settings.